The perennial conspiracy theory : reflections on the history of "The Protocols of the Elders of Zion" - Hagemeister, Michael 1951- (Routledge studies in fascism and the far right, 2022)
A Fake Conquers the World: The Protocols of the Elders of Zion -- The Protocols of the Elders of Zion in Court: The Bern Trials 1933-1937 -- On the Early History of the Protocols of the Elders of Zion: The Lost Copy of the Lenin Library -- The American Connection: Leslie Fry and the Protocols of the Elders of Zion -- The Antichrist as an Imminent Political Possibility: Sergei Nilus and the Apocalyptical Reading of the Protocols of the Elders of Zion -- The Third Rome Against the Third Temple: Apocalypticism and Conspiracism in Post-Soviet Russia